Acquired Cutis Laxa on the Upper Eyelids and Earlobes: A Case Report and Literature Review - Katsuren, Kyoko; Kuba, Ryogo; Kasai, Shogo; Shimizu, Yusuke (Archives of Plastic Surgery, 2022)
Acquired cutis laxa is a rare disease. Owing to few reports on the condition, no statistical data have been produced. Cutis laxa is characterized by drooping skin, caused by decreased levels of dermal elastin, leading to reduced skin elasticity. The disease usually emerges on the neck or trunk and spreads throughout the body; however, it rarely involves the extremities.2 Moreover, cases localized to the face are rare. The objective of this clinical case report was to highlight this unusual disease in a 24-year-old female, with localization on the face and neck. The patient underwent surgery for treatment of bilateral ear lobe and eyelid skin laxity.
Keywords: cutis laxa; elasticity; laxity; urticaria; surgery